2015
DOI: 10.9734/ijpss/2015/11581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Organic Nutrient Sources with NPK for Cashew Seedlings Growth towards Organic Cashew Farming in Nigeria

Abstract: This work was carried out in collaboration between both authors. Author RRI designed the Experiment, while authors RRI and OSOA carried out the field experimentation, data collection and analysis, literature review and write-up. Both authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…6-9) of the treated rice plants showed a significant increase (p < 0.001) when compared to BSC, NPK, and control plants. The results obtained were similar to a study made by Ipinmoroti and Akanbi in compost-treated cashew seedlings (organic nutrient sources) [32]. Lee et al [33] also reported that there was a significant increase in fresh weight of cabbage on application of farmyard manure (FYM).…”
Section: Resultssupporting
confidence: 86%
“…6-9) of the treated rice plants showed a significant increase (p < 0.001) when compared to BSC, NPK, and control plants. The results obtained were similar to a study made by Ipinmoroti and Akanbi in compost-treated cashew seedlings (organic nutrient sources) [32]. Lee et al [33] also reported that there was a significant increase in fresh weight of cabbage on application of farmyard manure (FYM).…”
Section: Resultssupporting
confidence: 86%